2017
DOI: 10.4209/aaqr.2016.09.0421
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Characterization and Particle Scrubbing Efficiency of Underwater Operations during Laser Cutting of Steel Components for Dismantling of Nuclear Facilities

Abstract: The goal of this article is to provide results on aerosol particles emissions of a laser Nd:YAG cutting technique used for the decommissioning of nuclear facilities. In particular, the study aims at characterizing the aerosol emitted during the cutting of steel specimens of different thicknesses and to study particulate emissions for cuts in air and under water. To do so, we calculate the emitted aerosol mass per unit area of cut. Overall, it was found that the mass of aerosol per unit area of cut by laser cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The increase in mass median diameter can be interpreted by more agglomeration of fine particles due to presence of water, this phenomenon being studied and explained through recent simulations [31]. Generally, these results are consistent with previous study of aerosols generated by laser cutting of stainless steel and characterized by submicron particle sizes [32].…”
Section: Mass and Chemical Element Size Distributionsupporting
confidence: 87%
“…The increase in mass median diameter can be interpreted by more agglomeration of fine particles due to presence of water, this phenomenon being studied and explained through recent simulations [31]. Generally, these results are consistent with previous study of aerosols generated by laser cutting of stainless steel and characterized by submicron particle sizes [32].…”
Section: Mass and Chemical Element Size Distributionsupporting
confidence: 87%
“…Iron, chromium, and nickel were found in more than 50% in the samples. Peillon et al [89] studied the aerosol particle emissions of a Nd/YAG laser cutting technique used for the decommis-sioning of nuclear facilities. It was found that the mass of aerosol per unit area of laser cutting decreased when the laser power and cutting speed increased.…”
Section: Particle Mattermentioning
confidence: 99%
“…Concern is raised in terms of potential health risks for exposed workers, in particular in mines, during nuclear fuel cycle operations, and dismantling of nuclear facilities (Anderson et al, 2016;Samson et al, 2016). These activities can result in particle resuspension or direct emission of aerosols (Peillon et al, 2017;Chae et al, 2019) in the air in workplace areas.…”
Section: Accepted Manuscriptmentioning
confidence: 99%